2006
DOI: 10.1037/1528-3542.6.4.670
|View full text |Cite
|
Sign up to set email alerts
|

Must interesting things be pleasant? A test of competing appraisal structures.

Abstract: Abstract:Appraisal theories have emerged as a powerful perspective on the elicitation and differentiation of emotional experience (Ellsworth & Scherer, 2003). Given the general acceptance of the appraisal approach, a central task for modern appraisal research is to refine and reconcile the predictions made by appraisal models. The agreement among different appraisal theories is substantial, yet there are cases in which different theories make inconsistent predictions. To date, few studies have directly compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
147
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(167 citation statements)
references
References 32 publications
17
147
1
2
Order By: Relevance
“…These scales measured feelings of interest (interesting-uninteresting, boring-exciting) and confusion (confusing-clear, perplexingobvious) and the appraisals of novelty-complexity (simple-complex, unfamiliar -familiar, common-unusual) and comprehensibility (comprehensible-incomprehensible, easy to understand-hard to understand). Similar items have been used in past research (see Silvia, 2005a;Turner & Silvia, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…These scales measured feelings of interest (interesting-uninteresting, boring-exciting) and confusion (confusing-clear, perplexingobvious) and the appraisals of novelty-complexity (simple-complex, unfamiliar -familiar, common-unusual) and comprehensibility (comprehensible-incomprehensible, easy to understand-hard to understand). Similar items have been used in past research (see Silvia, 2005a;Turner & Silvia, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, novelty appraisal and high coping potential appraisal does not predict the experience of liking (Ellsworth & Smith, 1988;2005b;Turner & Silvia, 2006). Furthermore, the appraisal structure of interest means that interest is not necessarily elicited by pleasant stimuli.…”
Section: Appraisal Structure and Motivational Functions Under Appraimentioning
confidence: 87%
“…Correspondingly, research has shown that novelty-complexity appraisal may evoke the emotion of interest (Silvia, 2005a(Silvia, , 2005b(Silvia, , 2008a(Silvia, , 2013Silvia, Henson, & Templin, 2009;Turner & Silvia, 2006). Furthermore, novelty-complexity appraisal can also predict the experience of interest beyond individual differences such as curiosity and openness to experience (Silvia, 2005b(Silvia, , 2008a.…”
Section: Emotional Responses To Perceived Design Newnessmentioning
confidence: 99%
See 2 more Smart Citations